2017
DOI: 10.3390/biomedicines5010003
|View full text |Cite
|
Sign up to set email alerts
|

Taking a Stab at Cancer; Oncolytic Virus-Mediated Anti-Cancer Vaccination Strategies

Abstract: Vaccines have classically been used for disease prevention. Modern clinical vaccines are continuously being developed for both traditional use as well as for new applications. Typically thought of in terms of infectious disease control, vaccination approaches can alternatively be adapted as a cancer therapy. Vaccines targeting cancer antigens can be used to induce anti-tumour immunity and have demonstrated therapeutic efficacy both pre-clinically and clinically. Various approaches now exist and further establi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
31
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 131 publications
0
31
0
1
Order By: Relevance
“…The expression of CTAs in adult human organs is limited to immune‐privileged sites, e.g. the testis and, for some CTAs, occasionally the placenta and the brain . In this study, we have shown that PRAME, which is a highly immunogenic CTA, is expressed in 83% of SDCs, but in none of the background tissues, e.g.…”
Section: Discussionmentioning
confidence: 71%
See 4 more Smart Citations
“…The expression of CTAs in adult human organs is limited to immune‐privileged sites, e.g. the testis and, for some CTAs, occasionally the placenta and the brain . In this study, we have shown that PRAME, which is a highly immunogenic CTA, is expressed in 83% of SDCs, but in none of the background tissues, e.g.…”
Section: Discussionmentioning
confidence: 71%
“…the testis and, for some CTAs, occasionally the placenta and the brain. 21,51 In this study, we have shown that PRAME, which is a highly immunogenic CTA, is expressed in 83% of SDCs, but in none of the background tissues, e.g. salivary glands, ICs, and stromal cells.…”
Section: Discussionmentioning
confidence: 74%
See 3 more Smart Citations